CONCERNING CULTURAL AND POLITICAL MOVEMENT; THE ROLE OF INTELLECTUAL AND CIVIL SOCIETY IN GRISHAM’S THE STREET LAWYER - Nasrullah, Nasrullah (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2018)
This paper is about the role of intellectuals and America’s civil society movement in the struggle of poor people and the homeless in Washington, USA, to claim their rights in Grisham’s The Street Lawyer. Both of these are called cultural and political movement. The author analyzes the discrepancy in USA in Reagan’s era. The interesting aspect of the novel is the role of legal clinic for homeless and the intellectual from NGO and social organization constructed in the novel. This paper uses genetic structuralism in analysis. Aspect of intrinsic and extrinsic of the work is the object of material of the analysis. Otherwise, the theories about intellectual and civil society movement by Antonio Gramsci are the extrinsic tools to describe how the social condition in that era is. The results of the analysis indicates the discrepancy in America, especially in Washington DC. The street lawyer and the intellectuals of some social organizations have the significant roles as the part of America’s social movement in creating equality and social welfare for all. Those case are founded in the analysis of the novel.